Exámen Especial a las cuentas ingresos y gastos en la Unidad Educativa Fiscomisional José María Vélaz S.J de la Ciudad de Loja, Período 01 de Enero al 31 de Diciembre del 2014 - Suárez Barba, Liliana Elizabeth (2017)
The present work titled "SPECIAL EXAMINATION TO THE ACCOUNTS REVENUES AND EXPENSES IN THE FISCOMISIONAL EDUCATIONAL UNIT" JOSÉ MARÍA VÉLAZ SJ, OF THE CITY OF SHOP, PERIOD 01 JANUARY TO 31 DECEMBER 2014 "was developed based on the provisions In the Regulation of Academic Regime of the National University of Loja, as a prerequisite to elect the Degree and Title of Engineer in Accounting and Public Accountant Auditor Audit. In order to comply with the objectives set, the methodology of the financial audit phases oriented to the special examination was applied; This is: Phase I, preliminary knowledge, obtaining a general approach of the entity; Phase II, planning, where information was collected in the preliminary planning showing the activities carried out by the educational unit, then in Phase III, execution of results, tests and procedures were applied to the accounting records of the accounts examined in the program The internal control was evaluated, the findings developed and supported with sufficient and competent evidence based on audit criteria. In Phase IV, communication of results, a final report was prepared summarizing comments, conclusions and recommendations to take necessary corrective measures to help achieve goals and objectives. And with the help of the materials, methods and procedures that were the main tools to execute the field work. 5 The main results obtained show internal control weaknesses such as: absence of an accounting process that provides reliable and timely financial information; Lack of a bank account to allow greater operational control of the income and expenses of the Educational Unit; Lack of delivery of authorized vouchers that support the transactions carried out in the provision of services, neglect in the file of source documentation that allows to preserve and adequately protect the documents, in order to prolong their use in optimal conditions during the time required by law ; Non-existence of labor contracts that underpin the agreements and working conditions of both parties; Nonconformity in the system of payment of wages or salaries that achieves a better work environment in the employees; Non-compliance in the payment of provisions and monthly benefits according to the Law and current legislation that establishes the improvement of the salary welfare of the teachers of the educational center; Non-existence of lease contracts of the establishment where the educational unit operates, stating the value established during the established period of time, so as not to give rise to unexpected variations by any of the parties; Situations that have been issued in a report to the Administrative Coordinator to make decisions that lead to better management and development of the unit